DZIKIR ROTIBUL ATTOS SEBAGAI SARANA PENDIDIKAN PEMBERSIHAN JIWA DALAM TASAWUF DI PP. DARUT TAUHID GENGGONG PROBOLINGGO - Ahkam, Muhammad Hafidzul; Muzakki, Ahmad; Arifin, Miftahul (Jurnal Al-Fatih, 2025)
Humans as creatures of Allah Subhanahu wa Ta'ala have two important dimensions, namely the material dimension (physical) and the soul dimension (spiritual). Both are interrelated and require balance in everyday life. The material dimension is related to worldly needs, such as eating, drinking, and clothing, while the soul dimension focuses more on inner peace and tranquility. One way that is believed to be able to cleanse the soul in the Islamic tradition is through dhikr, one of which is the Rotibul Attos dhikr developed by Al-Habib Umar bin Abdurrahman Al-Attas. This study aims to examine the role of Rotibul Attos dhikr as a means of cleansing the soul from a Sufism perspective, especially at the Darut Tauhid Genggong Probolinggo Islamic Boarding School. The method used is field research with a qualitative approach, through direct observation and interviews with the boarding school supervisor. The results of the study indicate that the practice of Rotibul Attos can have a positive impact on students, such as inner peace, increased faith, and the formation of better morals. In addition, this dhikr also functions as a spiritual fortress that protects oneself from negative influences. This study also identifies the right ways to practice this dhikr to obtain maximum benefits, by emphasizing sincere intentions and routine implementation at the recommended times. This study contributes to the understanding of the importance of dhikr in Sufism as a means to improve the soul and improve the quality of individual spirituality.